Tolerances robežu izpratne globalizācijas procesu kontekstā - Kravale, Dace (Latvijas Universitāte, 2008)
Globalizācijas apstākļos, kad Rietumu sabiedrību sociālās struktūras īpatnību un ekonomiskās attīstības nosacījumu kombinācija paredz aizvien lielāku migrācijas procesu ietekmi uz sabiedrības locekļu etnisko, kulturālo, reliģisko un lingvistisko piederību, tolerances jautājumi gūst aizvien pieaugošu sociālo nozīmību. Šī darba izstrādes pamatā ir sekojoši problēmjautājumi: līdz ar migrācijas procesu pieaugošo ietekmi globalizācijas apstākļos, tolerances un tās robežu jautājumi kļūst par nozīmīgu mūsdienu Rietumu sabiedrības dienas kārtības sastāvdaļu. Tomēr tolerances jēdziens nav aplūkojams tikai globalizācijas procesu kontekstā. Tolerances un tās robežu jautājumi ir nodarbinājuši politikas teorijas un politiskās filozofijas autorus jau sākot no 16. gadsimta. Sākotnēji tolerances idejas ģenēze ir saistīta ar reliģiskās tolerances pamatojuma izstrādi, kura nepieciešamību noteica reliģisko vajāšanu izplatība Eiropā. Atšķirībā no mūsdienām, sākotnēji tolerances un tās robežu jēdziena izpratne neparedzēja sasaisti ar demokrātijas ideju. Saskaņā ar iepriekš minēto, tiek izvirzītas divas hipotēzes. Pirmā hipotēze: migrācijas procesi, kas ir neatņemama globalizācijas procesu sastāvdaļa, padara tolerances jautājumus par īpaši nozīmīgiem mūsdienu Rietumu sabiedrībā un aktualizē jautājumu par tolerances robežām. Otrā hipotēze: tolerances un tās robežu izpratnes attīstību raksturo objektīva nepieciešamība pēc sasaistes ar demokrātijas ideju, ko apliecina arī tolerances jēdziena ģenēze. Lai pierādītu izvirzītās hipotēzes, tika formulēti sekojoši darba mērķi: (1) analizēt globalizācijas un migrācijas procesu ietekmi uz mūsdienu Rietumu sabiedrību, atklājot tolerances un tās robežu jautājumu aktualizācijas cēloņus, kā arī (2) aplūkot tolerances jēdziena veidošanos modernajā Rietumu politiskajā domā, īpašu uzmanību pievēršot tolerances un demokrātijas sasaistei. Lai gan mūsdienās tolerance tiek aplūkota kā viena no demokrātijas pamatvērtībām, dažādo tolerances izpratņu pastāvēšana nosaka šo divu jēdzienu savstarpējās mijiedarbības neviennozīmību. Tolerances pastāvēšana sabiedrībā pati par sevi nenodrošina demokrātiskas politiskās kultūras atražošanos. Lai nodrošinātu liberālās demokrātijas ilgtspējību globalizācijas apstākļos, ir nepieciešama plašāka tolerances izpratne, kas iekļauj integrācijas un kopīgas demokrātiskās līdzdalības elementus.

SUMMARY In globalized conditions when processes of migration are creating growing ethnic, religious and cultural diversity the social importance of the problems of tolerance and its limits cannot be overestimated. Globalization reveals itself not only through flows of goods, services, finance and technologies. It also implies substantial shifts in the spatial and temporal contours of human life resulting in major alterations in the understanding of key questions of normative political theory. In the context of this work the most crucial question concerns the impact of globalization on conditions of modern Western democracy. One of the most important advantages of contemporary technological development is the appearance of novel high-speed forms of travel. Peculiarities of social structure in Western democracies and the logic of economic development require increasing demand for migrant workforce that Western societies are not able to provide due to the low birth rates. But if immigrants are to stay (which mostly is the case) the challenges their different historic, ethnic, religious, linguistic and cultural backgrounds pose to the traditional modes of operation of once comparatively culturally homogeneous liberal democracies cannot be ignored. Thus the first hypothesis of this work is the following: migration flows as an integral part of the whole process of globalization increase the salience of the matters of tolerance in contemporary Western society and pose the question concerning the limits of tolerance. Historically the origins of the concept of tolerance are tied to the attempts to set down arguments in order to ensure promotion of religious tolerance. As political theorists and philosophers of the 16th and the following centuries started to formulate principles of religious tolerance, there was no claim for democracy involved. In contrast to the early liberal thinkers, nowadays the concept of tolerance and its limits is intimately connected to the idea of democracy. So the second hypothesis of this work follows: the evolution of the concept of tolerance and its limits is characterized by necessary condition for association with the idea of democracy reflected also by the genesis of the concept of tolerance. In accordance with the afore mentioned the aims of this work are: (1) to provide an analysis of the impact of globalization and migration flows on contemporary Western society thus revealing the causes of the actualization of the problems of tolerance and its limits and (2) to provide an overview of the genesis of the concept of tolerance in modern Western political thought minding the connection between tolerance and democracy. Recent theoretical debate about democracy concerns the disillusionment and alienation of the citizenry that fuels speculations about the demise of the model of liberal democracy. Although open challenges to the liberal democratic model are very few there sill exists a significant concern about the future prospects of democracy. In addition to the problems outlined increasing cultural diversity of Western democracies poses another challenge to the cohesion of democratic community that can be overcome by incorporating a comprehensive notion of tolerance. Though nowadays tolerance is viewed as one of the basic values of democracy the existence of a number of different understandings of the concept of tolerance determines the complex interplay of the ideas concerned. In order to ensure the sustainability of liberal democracy in conditions of globalization a broad understanding of tolerance is required. Tolerance in this context means something more than a restraint from suppression of difference stemming from realization of its inevitability. The understanding of tolerance in contemporary democratic context means intensive interaction and mutual cooperation among different members of political community thus creating common democratic political culture.
Understanding the limits of tolerance in globalized context
Keywords: Politikas zinātne (politoloģija)